The predictive utility of neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in screening of coronary heart disease in end-stage renal disease patients undergoing dialysis: A cross-sectional study - Wachid Putranto, Devi Nurul Baeti, Ananto Wibisono, Aryo Suseno, Heru Sulastomo, Nurhasan Agung Prabowo, Yeremia Suryo Pratama (Journal of Applied Pharmaceutical Science, 2023)
End-stage renal disease (ESRD) patients undergoing dialysis are at increased risk for developing coronary heart disease (CHD). Recent studies have shown that neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) may be used to determine individuals at high risk of CHD. This study aims to examine whether NLR and PLR could predict the risk of CHD characterized by elevated carotid intima-media thickness (CIMT) in ESRD patients. Our cross-sectional study includes patients with ESRD on hemodialysis (HD)- or continuous ambulatory peritoneal dialysis (CAPD)-based renal replacement therapy (RRT) at Moewardi General Hospital in Surakarta, Indonesia, from January to July 2022. The primary outcome in this study is the presence of a high risk of CHD characterized by CIMT ≥1 mm, and the main predictors used in this study are NLR and PLR. Among the patients (n = 72), the analysis showed that NLR [OR 1.474 (95% CI: 1.031–2.106); p = 0.033] had a statistically significant association with the CIMT status. Group analysis showed NLR association with CIMT on CAPD patients [OR 5.957 (95% CI: 1.189–29.847); p = 0.030]. The association was not significant with PLR (p > 0.05). Optimal cut-offs were established in NLR ≥2.72 area under the curve (AUC: −0.909; p = 0.001; sensitivity = 95.45%, specificity = 83.33%) and PLR ≥93.09 (AUC: −0.969; p = 0.001; sensitivity = 90.91%, specificity = 83.33%) in CAPD patients, with lower AUC and specificity values in the analysis of both RRTs and HD patients. NLR and PLR are excellent yet simple predictors of CHD risk in ESRD patients undergoing dialysis.
Keywords: Cardiovascular disease, chronic kidney failure, coronary heart disease, diagnosis, peritoneal